DETERMINASI MINAT NASABAH MENABUNG DI BANK SYARIAH MILIK PEMERINTAH - Chaniago, Nuraini; R. Adjeng Entaresmen (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2022)
This study aims to examine the factors that influence customer interest in saving at Islamic banks. Samples were taken from 111 respondents with the results of data quality testing showing all the indicators that make up the variables in this study, namely service quality, religion and promotion. valid and reliable so that it can be continued for hypothesis testing. To test the hypothesis, the Multiple Linear Regression analysis tool is used. The results of hypothesis testing prove that service quality, religion, and promotion together have a direct effect on interest in saving in Islamic banks. Religion and promotion partially have a significant effect on interest in savings in Islamic banks while the service variable is not proven to have an effect on interest in savings.